ASSESSMENT OF CRITICAL BUTYRIC ACID CONCENTRATIONS IN FECES OF PATIENTS ON ENTERAL TUBE FEEDING IN INTENSIVE CARE UNITS - ALEKSANDR M. Zatevalov; VLADIMIR A. Aleshkin; EVGENIYA P. Sel'kova; TATYANA A. Grenkova (Фундаментальная и клиническая медицина, 2017)
Aim. To determine the critical butyric acid concentrations in the feces of patients on enteral tube feeding. Materials and Methods. We investigated oropharyngeal and gut microbiota of 31 patients admitted to intensive care unit and further supplied with enteral tube feeding. Quantication of microorganisms was performed by seeding into liquid agar medium. Activity of oropharyngeal and gut microbiota was determined by measuring concentrations of short-chain fatty acids using gas-liquid chromatography. Results. At the fecal butyric acid concentration of 2.2 mmol/g, a ratio of fecal levels of acetic, propionic, and butyric acids (C2:C3:C4) was 72:17:11, with a structural index of 0.56. Below fecal butyric acid concentration of 2.2 mmol/g, a proportion of acetic acid decreased linearly, with a decrease in structural index. Conclusions. Decrease in fecal butyric acid concentration < 2.2 mmol/g impairs activity of gut microbiota and induces further metabolic changes in the gut.